Fish Assemblage Concerning Physciochemical and Geomorphological Characteristics of Barak River, India - Rai , Prabhakar; Kumar, J. S. Yogesh; Sen , Arya; Bhattacharjee , Saurav (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This study investigated the fish population, environmental characteristics, microhabitats, and soil erosion along the Barak River in Manipur and Assam. The survey covered 18 sites spanning from Maram in Senapati district, Manipur, to Badarpur in Karimganj district, Assam. The assessment involved analysing six physciochemical parameters and collecting fish specimens, focusing on human activities affecting different sections of the river. The environmental conditions varied significantly between two distinct geographical regions: the hilly area in Manipur and the plains in Assam. The river exhibited narrowness, shallow depths, rapid flow, and a substrate composed of stones and gravel in the hilly region of Manipur. Conversely, in the plains of Assam, the river was wider, slower flowing, deeper, and featured a substrate consisting of silt and clay. Bank erosion and river meandering were prevalent in the plains, which were densely populated and extensively cultivated. The survey documented a total of 35 fish species from 15 families and 7 orders. Interestingly, the distribution pattern indicated an absence of certain fish species in one region that were present in the other. The highest species diversity was recorded in Namtiram, Tamenglong district, Manipur, for the hilly stretch, and Srikona, Cachar district, Assam, for the plains. Surprisingly, the study noted that physciochemical parameters had minimal influence on fish distribution; instead, it appeared that habitat and other environmental factors played a more significant role in regulating the presence of fish species.